Fungi in sands of Mediterranean Sea beaches of Israel—Potential relevance to human health and well‐being. Issue 11 (23rd August 2020) - Frenkel, Michael; Yunik, Yaron; Fleker, Marcelo; Blum, Shlomo E.; Sionov, Edward; Elad, Daniel; Serhan, Hanan; Segal, Esther
Abstract: Background: Sand of sea harbour bacteria that may cause enteric and other infections in humans, and are controlled by regulatory measures. Data on fungi in sea sand are scarce. Thus, an international group of mycologists was formed to explore fungal flora in sand of various waterbodies. Objectives: The aim was to explore fungal sand contamination in beaches of the Israeli Mediterranean Sea Coast, regarding possible impact on human health in three aspects: (a) faecal contamination, as judged by presence of the human enteric fungi; (b) contamination by fungi, causing dermal infections; (c) and the presence of moulds, causing respiratory allergies and pose a risk for infection in immunocompromised individuals. Methods: The study included sand screen of six urban beaches from north to south of the Israeli Mediterranean Coast. Sand samples were extracted by water, and the water wash was cultured and quantitated. The fungi were identified phenotypically, by MALDI‐TOF MS system and ITS sequencing. Results: The screen revealed that about 80% of the isolates were moulds and about 20% yeasts. The mould species included opportunistic pathogens and potential allergens: Aspergillus fumigatus, Fusarium and Mucorales species. Yeast isolates included Candida, Cryptococcus and Rhodotorula species. Conclusions: (a) Fungi are contaminating Israeli Mediterranean sand beaches; (b) the contaminating fungi include various yeast and mould species; (c) some of the yeasts and mould species found in sand are known opportunistic pathogens, or respiratory allergens; (d) the data could serve as basis for initiating regulatory measures to control fungal contamination of sand for the benefit of public health.